BREASTMILK HANDBOOK TO INCREASE KNOWLEDGE ABOUT BREASTFEEDING FOR WOMEN PREGNANCY - Dewi Andariya Ningsih; Miftakhur Rohmah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
ABSTRACT Breastfeeding is a natural activity of women who already have children and the Qur’an regards it as a command from Allah SWT because it is a form of an honor for women. The low coverage about giving breastfeeding in Islamic way is one of the factors of the mothers and families’ low knowledge about breastfeeding. One of the media that can be used to increase public knowledge about breastfeeding is the pregnancy handbook for pregnant mother. The purpose of this research was to develop the pregnancy handbook for pregnant mothers about breastfeeding that includes Islamic character values. The form of the research used was R&D method. The development of these teaching materials produced a handbook product for pregnant women to prepare exclusive breast milk. The results of this research were: the average pre-conference and post-conference scores increased by 54%, the results of material expert test were 3.3, the media expert assessment were 3.6. Furthermore, a significant test was concluded that there were differences between before and after being given the mother’s pregnancy handbook about breastmilk. Keywords: breastmilk, breastfeeding, handbook, Islamic.